Pan-cancer analysis identifies LIFR as a prognostic and immunological biomarker for uterine corpus endometrial carcinoma - Zhang, Fang; Wang, Yali; Li, Hongjuan; Li, Li; Yang, Xiaofeng; You, Xiaoyan; Tang, Lina (Frontiers in Oncology, 2023)
Background Leukemia inhibitory factor (LIF) exhibits significant tumor-promoting function of cancers, while its cognate receptor (LIFR) is considered as a tumor promotor or suppressor. The dysregulation of LIF and LIFR has been identified to be associated with the initiation, progression and metastasis for multiple cancer types. Although increasing studies revealed the indispensable critical role of LIFR in tumorigenesis for various cancers, there is no systematic analysis of LIFR yet. Methods In this research, we comprehensively analyzed the expression profile and prognostic values of LIFR and the correlation between LIFR with infiltration of immune cells and clinicopathological parameters across different tumor types using several bioinformatic tools. Moreover, we detected the effect of LIFR on Uterine Corpus Endometrial Carcinoma (UCEC) and evaluated the expression level of LIFR in clinical UCEC samples. Results We detected the aberrant expression of LIFR in cancers and its prognosis ability, especially in UCEC. Additionally, LIFR remarkably associated with immune infiltrating cells and checkpoint genes. Overexpression of LIFR suppressed the migration and invasion of UCEC cells in vitro. Conclusion Our pan-cancer detection data provided a novel understanding of the roles of LIFR in oncogenesis in tumors.